(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
Peste des Petits Ruminants (PPR) is a highly fatal viral disease of goat and sheep. This research work was done in 2017-2018 by executing, surveillance and epidemiological studies to determine present status of circulating PPR virus and its molecular characterization in different areas of Bangladesh. cELISA was conducted to detect the PPR antibody and RT-PCR also used for identification of N gene PPRV. Sera samples and nasal swabs were collected from eight (8) selected villages under Meherpur sadar upazila of Meherpur district on questionnaire basis. Considering two villages as control and six villages as treatment villages. The total 1860 sera were collected at pre vaccination, 21 days, 3 months, 6 months of post vaccination at these selected areas that tested by cELISA and 8035 goat and sheep were received locally produced PPR Vaccine. Baseline study showed that a total of 950 household rear goats in selected 8 villages where number of goats per household ranges from 4.0-5.0. Deworming was done before vaccination in the treatment villages. Pre-vaccination status of six (6) treatment villages were 55.95%, 50.76%, 37.68%, 41.12%, 44.62% and 43.26% in Chakshamnagar, kola, Amjupi, Amdah, Gopalpur and Chadbill respectively, whereas in the control villages (2) seropositive were 40.00% and 42.57% in Doforpur and Mayamari, respectively. Overall 44.90% goats were seropositive against PPR Virus in treatment villages before vaccination. The Sera was analyzed from 21 days, 3 months and 6 months of post-vaccinated goat and sheep from the treatment (6) villages showed the average herd immunity level of goats and sheep rose to 89.10%, 93.25% and 93.37% respectively whereas in the control villages seropositive goats was 38.14%, 43.98% and 35.64% respectively. Awareness building campaigns with villagers have been conducted involving both men and women through the training, meeting, regular visit of household, distribution of poster and leaflet. The mortality and case fatality rate recorded were 7.4% and 18.8%, respectively due to PPR outbreaks. In clinical case, total 59 nasal swabs were molecular characterized by RT-PCR and 41 (69.49%) samples were N gene positive. Among them, the highest presence of PPR virus was recorded at Meherpur sadar upazila 80.77% (21 out of 26) samples was positive. The result of RT-PCR indicates the PPR virus circulating in the different regions of Bangladesh. It is reflected that locally produced PPR vaccine confers sufficient herd immunity that can protect PPR disease in goat and sheep which helps to meet global PPR control programme. Asian Australas. J. Biosci. Biotechnol. 2019, 4 (2), 88-96